Stable Ectopic Expression of ST6GALNAC5 Induces Autocrine MET Activation and Anchorage-Independence in MDCK Cells - Chu, Chia (PLoS One, 2016)
The epithelial-mesenchymal transition (EMT) is a complex cancer progression that can boost the metastatic potential of transformed cells by inducing migration, loss of cell adhesion, and promoting proliferation under anchorage-independent conditions. A DNA microarray analysis was performed comparing parental anchorage-dependent MDCK cells and anchorage-independent MDCK cells that were engineered to express human siat7e (ST6GALNAC5). The comparison identified several genes involved in the EMT process that were differentially expressed between the anchorage-dependent and the anchorage-independent MDCK cell lines. The hepatocyte growth factor gene (hgf) was found to be over-expressed in the engineered MDCK-siat7e cells at both transcription and protein expression levels. Phosphorylation analysis of the MET receptor tyrosine kinase confirmed the activation of an autocrine loop of the HGF/ MET signaling pathway in the MDCK-siat7e cells. When MET activities were suppressed by using the small-molecular inhibitor drug PF-02341066 (Crizotinib), the anchorage-independent MDCK-siat7e cells reverted to the cellular morphology of the parental anchorage-dependent MDCK cells. These observations indicate that the MET receptor plays a central role in the growth properties of the MDCK cells and its phosphorylation status is likely dependent on sialylation. Further investigation of the downstream signaling targets in the MET network showed that the degree of MDCK cell adhesion correlated with secretion levels of a matrix metalloproteinase, MMP1, suggesting a role of metalloproteinases in the EMT process. These results demonstrate that in addition to its application in biotechnology processes, MDCK-siat7e may serve as a model cell for metastasis studies to decipher the sequence of events leading up to the activation of EMT.